THE INFLUENCE OF RELIGIOSITY, ECONOMIC PRESSURE, FINANCIAL MANAGEMENT, AND STRESS LEVELS TOWARDS FAMILY QUALITY OF LIFE DURING COVID-19 PANDEMIC IN INDONESIA - Azzara, Rana Chyntia; Simanjuntak, Megawati; Puspitawati, Herien (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
An increased number of coronavirus cases infection has resulted in instability of household, which has an impact on family quality of life (QoL), and the facts during Covid-19 pandemic are contrary to the structural-functional theory, which emphasizes system stability and balance. This study aims to analyze the effect of religiosity, economic pressure, stress levels, and family management on family QoL during the Covid-19 pandemic and to analyze family typology based on stress levels, economic pressure, and family QoL. This study uses a quantitative approach and voluntary sampling method with 270 respondents selected based on criteria of working mothers or homemakers with working husbands. The higher frequency of religiosity and the smaller the economic pressure, the lower risk of high-stress levels. The high-stress levels and economic pressure decrease the family QoL, but the QoL increase if the family can carry out good financial management. Increasing the frequency of religiosity would improve family QoL by reducing stress levels. The typology is dominated by economic pressure and low QoL, while the typology of stress level and balanced QoL is dominated by the best type (low-stress levels, high QoL) and both low types. Reduced economic pressure, improved financial management, and stress management are important to preserve or improve QoL.